Molecular cloning and characterisation of the two DNA components of tomato golden mosaic virus. - Bisaro, D M (1982)
We report the molecular cloning of the tomato golden mosaic virus (TGMV) genome in the E. coli plasmid pAT 153. The results of this work conclusively show that TGMV DNA consists of two components (designated A and B) of almost, but not exactly, the same size. Four different recombinant plasmids are described, two containing component A in opposite orientation and two containing component B in opposite orientation. Southern blot analysis revealed little sequence homology between A and B and showed both components to be equally represented in viral and intracellular DNA forms. Detailed restriction maps of the cloned DNAs are presented, and a comparison of these with digests of intracellular viral dsDNA indicates that the former are full-length faithful copies of TGMV DNA. This is the first report of the cloning of a geminivirus genome.